Contrasting emotional labor and burnout in civilian and sworn law enforcement personnel. Issue 2 (9th March 2020) - Adams, Ian T.; Mastracci, Sharon H.
Abstract : Purpose: This study introduces emotional labor into an analysis of multiple dimensions of burnout in sworn and civilian employees across three law enforcement agencies. Design/methodology/approach: Using data from a survey of law enforcement employees in a metropolitan police department, a full-service sheriff's department, and a state corrections agency located in the western United States ( n = 1, 921), we test the explanatory power of an emotional labor-based model of burnout. Findings: Results partially confirm the lone prior study to examine civilian and sworn personnel. Sworn and civilian employees experience variant levels of emotional exhaustion and depersonalization, though the underlying emotional labor correlates are significantly related to burnout for both groups. Further, we extend prior results by capturing multiple facets of burnout as well as contributing an emotional labor explanation for burnout, while controlling for individual demographic characteristics and agency type. Research limitations/implications: Law enforcement agencies rely upon non-sworn employees to support their missions. The experience of non-sworn law enforcement personnel is under-researched in both the emotional labor and law enforcement organizational literature. Burnout is a phenomenon that has high costs for both employees and organizations, particularly in the law enforcement context. Investigating the emotional labor experience of employees is critical for practitioners who are tasked with effectively managing both groups. Originality/value: One previous study has investigated the emotional labor of civilians in law enforcement and used community-level predictions for burnout. This study builds on those findings by capturing two facets of burnout rather than the lone gauge of burnout used in the previous study. Furthermore, we use an emotional labor model to investigate emotional exhaustion and depersonalization reported by sworn and civilian personnel.